Effects of river discharge and wave forcing on hydrodynamics in a seasonal dual-inlet estuary - Zhang, Zhaozi; Wang, Zhenlu; Liang, Bingchen; Jia, Yonggang; Liu, Xiaolei; Wu, Guoxiang (Frontiers in Marine Science, 2025)
This study employs the Delft3D coupled wave-current model to investigate the spatiotemporal variability of flow and salinity fields, and the mechanisms governing residual currents under varying runoff and wave conditions in an estuarine area on the southeastern coast of the Shandong Peninsula, China. Model calibration and validation using multi-source observational datasets confirm good agreement with measured water levels, currents, and waves. Results reveal pronounced seasonal variations in the estuarine flow field: in summer, runoff-driven flows enhance seaward surface currents, whereas winter flow fields are primarily tide-driven and vertically uniform. The residual current patterns show significant sensitivity to runoff magnitude and spatial configuration. Northern runoff induces robust surface outflow and bottom inflow across a wide estuarine region, while southern runoff is topographically constrained. The result of double-runoff case exhibits nonlinear interactions, including localized enhancement and cancellation of residual currents. Wave forcing modulates the vertical structure and magnitude of residual currents, especially in offshore and geomorphically complex areas, with stronger influence on longitudinal components. These findings clarify the interplay between seasonal hydrodynamics, runoff input, and wave dynamics, offering new insights into residual circulation mechanisms in seasonally dynamic estuaries.